Relentless progress : the reconfiguration of children's literature, fairy tales, and storytelling - Zipes, Jack, 1937- (Routledge, 2009)
In Relentless Progress, Zipes looks at the surprising ways that stories have influenced people within contemporary culture and vice versa. Among the many topics explored here are the dumbing down of books for children, the marketing of childhood, the changing shape of feminist fairy tales, and why American and British children aren't exposed to more non-western fairy tales.